Baltic *kalu̯ā “hill” - Blažek, Václav (Vilnius University Open Series, 2022)
The purpose of this contribution is to separate Baltic *kalu̯ā “hill” from Baltic *kalnas “mountain” and to connect it with Indo-Aryan *kū́lva-, Iranian *karu̯a- „thin-haired“; Greek *κόλϝος “docked, hornless”; Italic *kalau̯o- & *kalau̯ā “bald (head)”, and the Pre-Romance oronym *kalauos, besides the Gaulish cognomen calaua. The semantic shift from “bald” to “hill” is supported by numerous examples of “bald hills”.